2007
DOI: 10.1097/pgp.0b013e31803025cd
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Greater Expression of ER, PR, and ECAD in Advanced-Stage Low-Grade Ovarian Serous Carcinoma as Revealed by Immunohistochemical Analysis

Abstract: A 2-tier system that classifies ovarian serous carcinoma (OSC) as low grade or high grade is gaining acceptance. Women with low-grade OSC generally have higher 5-year survival rates than do women with high-grade OSC. We examined the expression of various markers to further understand the molecular differences between low-grade and high-grade OSCs: the potential therapeutic targets or prognostic markers Her-2/neu, estrogen receptor, and progesterone receptor (PR); the metastasis-associated markers cyclin D1 (BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 28 publications
6
73
1
1
Order By: Relevance
“…The expression of ER in ovarian serous carcinomas in our study was not associated with tumor grade or neoadjuvant chemotherapy. In contrast to our observation, higher ER and E-cadherin expression was reported for low-grade ovarian serous carcinomas than for high-grade ovarian serous carcinomas by Wong et al 35 It is possible that we could not detect a significant difference in ER expression between low-and high-grade ovarian serous carcinoma in any of the markers results from limited sample size of low-grade tumors in our study. O'Neill et al 36 found significantly higher expression of p53 and HER2/neu in high-grade ovarian serous carcinoma when compared with low-grade tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…The expression of ER in ovarian serous carcinomas in our study was not associated with tumor grade or neoadjuvant chemotherapy. In contrast to our observation, higher ER and E-cadherin expression was reported for low-grade ovarian serous carcinomas than for high-grade ovarian serous carcinomas by Wong et al 35 It is possible that we could not detect a significant difference in ER expression between low-and high-grade ovarian serous carcinoma in any of the markers results from limited sample size of low-grade tumors in our study. O'Neill et al 36 found significantly higher expression of p53 and HER2/neu in high-grade ovarian serous carcinoma when compared with low-grade tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent study, Wong et al [27] used immunohistochemical analysis to compare the expression of various markers in tumor samples from women with advancedstage low-grade serous ovarian carcinoma and high-grade serous ovarian carcinoma. These investigators reported that the low-grade tumors expressed signifi cantly higher levels of estrogen receptor, progesterone receptor, and Ecadherin than the high-grade tumors did.…”
Section: Pathologic and Molecular Characteristicsmentioning
confidence: 99%
“…70% of relapses. 7,10,11 In addition, in both tumor types, women # 35 years of age have worse outcomes compared with older women. 5 On the basis of our clinical experience, LGSC does not seem to be completely resistant to platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%